2004
DOI: 10.1128/jcm.42.8.3505-3512.2004
|View full text |Cite
|
Sign up to set email alerts
|

Species of the Family Helicobacteraceae Detected in an Australian Sea Lion ( Neophoca cinerea ) with Chronic Gastritis

Abstract: We describe the first case of gastritis in a male Australian sea lion (Neophoca cinerea) in which members of the family Helicobacteraceae, particularly the genus Wolinella, were detected. The sea lion exhibited clinical signs of gastrointestinal disease, including abdominal pain, lack of appetite, and lethargy. Examination of one ileal and five gastric biopsy specimens collected over a 10-year period revealed persistent fibrosis and/or superficial focal erosion and ulceration of the lamina propria. Spiral-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…aurati has been associated with chronic gastritis, intestinal metaplasia and one reported case of gastric adenocarcinoma in hamsters however role these organisms play in the etiology of these diseases requires further elucidation (Patterson et al 2000a, b;Nambiar et al 2005). The role of other gastric Helicobacter species in other animals such as H. cetorum in marine mammals and ''Candidatus H. bovis'' in ruminants is currently unknown though gastric ulcers are found in these animals (De Groote et al 1999b;Harper et al 2002a;Oxley et al 2004;Haesebrouck et al 2009). …”
Section: Disease Association In Animalsmentioning
confidence: 95%
See 1 more Smart Citation
“…aurati has been associated with chronic gastritis, intestinal metaplasia and one reported case of gastric adenocarcinoma in hamsters however role these organisms play in the etiology of these diseases requires further elucidation (Patterson et al 2000a, b;Nambiar et al 2005). The role of other gastric Helicobacter species in other animals such as H. cetorum in marine mammals and ''Candidatus H. bovis'' in ruminants is currently unknown though gastric ulcers are found in these animals (De Groote et al 1999b;Harper et al 2002a;Oxley et al 2004;Haesebrouck et al 2009). …”
Section: Disease Association In Animalsmentioning
confidence: 95%
“…W. succinogenes was detected in gastric biopsies from a sea lion with gastritis (Oxley et al 2004). In 2003, Bohr et al detected ''Candidatus Wolinella africanus'' DNA from esophageal mucosa biopsies of South African patients suffering from stenosing squamous cell carcinoma (Bohr et al 2003).…”
Section: Pathogenicity Clinical Relevancementioning
confidence: 98%
“…However, complete genome sequencing of W. succinogenes has revealed that this organism shares 1,269 of its 2,046 genes with H. pylori and Campylobacter jejuni, many of which were identified as virulence factors (2). Interestingly, W. succinogenes was recently detected in gastric biopsies from a sea lion with gastritis (17). Our finding of W. succinogenes in the intestinal tract of children with gastrointestinal symptoms suggests that the status of this organism as a nonpathogen may need to be reevaluated.…”
Section: Fig 2 Fish Analysis Of Sections Cut From Biopsy Samples (A)mentioning
confidence: 99%
“…This has led researchers to question the nonpathogenic status of W succinogenes. 38 However, the Wolinella spp identified in the dogs of the study reported here clustered more closely with W succinogenes than with Candidatus W africanus. 37 A new putative Wolinella sp has also been identified in the stomach of a sea lion with gastritis.…”
Section: Discussionmentioning
confidence: 54%